Integration of blockchain technology and prioritization of deployment barriers in the blood supply chain - Ieva Meidute-Kavaliauskiene; Amir Karbassi Yazdi; Amir Hedayati Mehdiabadi (Logistics, 2022)
Background: This research aims to prioritize the blood supply hub for coping barriers of implementation blockchain (BC) in supply chain management (SCM). Nowadays, blood supply is a crucial matter that plays an essential role in people's lives. Hence, tracing the supply of blood is very substantial. One of the ways for the SCM of blood supply is a blockchain system. It shows how all traces of the SCM stream can flow from raw material to receiving blood into end users. However, there are many barriers to the implementation of blockchain. None of the companies can design improvement projects to resolve these barriers because of a lack of rare resources, such as human resources (HR), budget, information, etc. Methods: Barriers are first extracted from previous studies and interviews with experts in this study. Then, these barriers are customized for this case study by the Delphi method. Then, these blood supply hubs are ranked by measurement alternatives and ranking according to the compromise solution (MARCOS) method. Since this method needs primary weight, the best-worst method (BWM) is applied to obtain this weight. Result: Results have pointed out that business owners' unwillingness was the highest priority among the nine barriers. Conclusions: Additionally, implementing blockchain for SCM of blood supply requires paying more attention to business owners' unwillingness barriers and resolving them. Furthermore, hub 4 is faced with many problems in tackling barriers to implementing SCM blockchain.
Keywords: 650; best-worst method; blockchain; blood supply hub; MARCOS method; supply chain management